(untitled) (Jurnal Pustaka, 2025)
This research aims to (1) describe the implementation of the Numbered Heads Together (NHT) Cooperative learning model assisted by interactive board card media affects the improvement of mastery of hiragana letters in class X students of Banyuatis Tourism Vocational School. and (2) describe students’ perceptions of the Numbered Heads Together (NHT) Cooperative learning method assisted by interactive board card media.The research subjects were 24 students of class X Hospitality of Banyuatis Tourism Vocational School. The data collection methods used included tests, observations, and questionnaires, which were then analyzed using quantitative descriptive methods. The results showed that (1) students’ mastery of Hiragana letters increased through the application of the NHT type cooperative learning method with interactive board card media. Based on the pre-test results, the average student score was 51.5 with a completeness percentage of 12.5%. After cycle I, the average score increased to 65.9 with 45.8% completeness. In cycle II, the average score increased to 70 with 70.8% completeness. After cycle III, the average score increased significantly to 86.9 with 89.83% completeness. (2) Students’ responses to the application of the NHT type cooperative method were also positive, with an average score of 4.0 in cycle I, increased to 4.2 in cycle II, and reached 4.3 in cycle III.